Blue, Barry & Pancakes - Abdo, Dan; Jason (Jason Linwood Patterson) (2021)
"Blue, Barry, and Pancakes are best friends, but sometimes friends make mistakes. One day, when the gang goes to the beach, Barry and Pancakes lose Blue's beloved beach ball. They come up with a plan to get it back, but things go way off course. Now, these pals will have to go inside a giant whale's stomach, crash a pool party on an alien spaceship, and survive Duckzilla's volcanic birthday bash if they ever hope to see Blue's beach ball again!" --publisher's website.
Keywords: Best friends -- Comic books, strips, etc; Beach balls -- Comic books, strips, etc; Lost articles -- Comic books, strips, etc; Rabbits -- Comic books, strips, etc; Frogs -- Comic books, strips, etc; Worms -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Frogs -- Fiction; Rabbits -- Fiction; Worms -- Fiction; Friendship -- Fiction; Cartoons and comics; Beach balls; Best friends; Friendship; Frogs; Lost articles; Rabbits; Worms; Comics (Graphic works); Graphic novels; Humorous comics; Comics (Graphic works); Graphic novels; Humorous comics